Characterization of the self-assembly process of hydrophobically modified dextrin - Gonçalves, Catarina (2008)
Hydrophobized dextrin, randomly substituted by long alkyl chain (C16), forms stable hydrogel nanoparticles by self-assembling in water. Hydrophobic chains, distributed along the polymer backbone, promote the formation of hydrophobic microdomains within the nanoparticles. The influence of degree of substitution with hydrophobic chains (DSC16) on nanoparticles size, colloidal stability, density, aggregation number and nanoparticle weight was studied. Size distribution was also evaluated at different pH, urea concentration and ionic strength conditions. As shown by dynamic light scattering and transmission electron microscopy, the particles are spherical having a diameter of about 20 nm. The more substituted polymer forms more densely packed hydrophobic microdomains, such that the colloidal stability (in water and PBS buffer) of nanoparticles is increased. The knowledge of the aggregate building process and the characteristics of the nanoparticles are crucial for the design of drug delivery systems.